A DECISION SUPPORT SYSTEM FOR SELECTION OF SOCIAL WELFARE ASSISTANCE RECIPIENTS IN BENGKAYANG REGENCY USING WEIGHTED PRODUCT ALGORITHM - Yuliana Yuliana; Christian Cahyaningtyas; Elvis Pawan (PT. GWEX NET PUBLISHER, 2026)
PPKS is a priority group of recipients of social welfare programs based on Law Number 11 of 2009. The implementation of social services for individuals and groups requires high accuracy in identifying aid recipients according to the standards of the Minister of Social Affairs Regulation Number 16 of 2019. This study aims to build a Decision Support System (DSS) to assist the Bengkayang Regency TKSK team in determining the priority of aid recipients objectively. The method applied is Weighted Product (WP) involving 5 main criteria. The research stages include data collection through observation, basic data design, and system implementation. The results of sample analysis on the data show that the highest final value (V) was obtained by the category of families with social psychological problems (0.271738), followed by the category of neglected age (0.208379), the poor (0.201281), and people with disabilities (0.162531). The highest ranking produced by the system places the alternatives Salamah, Bulhaji, Satem, Keisha, and Sensius as the main priority. The implementation of this data-based system has proven to be able to accurately align manual calculation results with the system, so that it can be an effective consideration instrument for making decisions regarding the selection of social assistance.